2017
DOI: 10.1620/tjem.242.137
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Significance of Measuring Vascular Endothelial Growth Factor for the Differentiation between Malignant and Tuberculous Pleural Effusion

Abstract: Malignancy and tuberculosis are common causes of lymphocytic exudative pleural effusion. However, it is occasionally difficult to differentiate malignant pleural effusion from tuberculous pleural effusion. Vascular endothelial growth factor (VEGF) is a critical cytokine in the pathogenesis of malignant pleural effusion. Endocan is a dermatan sulfate proteoglycan that is secreted by endothelial cells. Importantly, endocan mediates the vascular growth-promoting action of VEGF. The aim of this study was to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Most of these previous studies were performed in patients with acute pulmonary diseases such as acute lung injury, acute respiratory distress syndrome, community-acquired pneumonia, pulmonary embolism, lung cancer, and pleural effusion. 25 32 There are only two studies in stable lung diseases, sarcoidosis and OSA. 33 , 34 These studies reported higher endocan levels in sarcoidosis and OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these previous studies were performed in patients with acute pulmonary diseases such as acute lung injury, acute respiratory distress syndrome, community-acquired pneumonia, pulmonary embolism, lung cancer, and pleural effusion. 25 32 There are only two studies in stable lung diseases, sarcoidosis and OSA. 33 , 34 These studies reported higher endocan levels in sarcoidosis and OSA.…”
Section: Discussionmentioning
confidence: 99%
“…The patient developed pleural dissemination and malignant pleural effusion. High VEGF levels are reported in malignant pleural effusions with different cancer origins, and VEGF signals have pathogenic roles in developing malignant pleural effusions [ [6] , [7] , [8] , [9] ]. Bevacizumab, a humanized anti-VEGF monoclonal antibody, added to a standard therapy is preferable for patients with non-small lung cancer with malignant pleural effusion [ 10 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, a metaanalysis pooled the results of ten available studies, concluding that the diagnostic sensitivity and specificity of VEGF were 0.75 and 0.72, respectively (27). Some other studies on this topic have since been published (28)(29)(30)(31), so that an updated meta-analysis may be needed to re-assess the diagnostic accuracy of VEGF in MPE.…”
Section: Vascular Endothelial Growth Factor (Vegf) and Its Soluble Rementioning
confidence: 99%